Detection and evaluation of Caesium-137 point source using silicone photomultiplier sensor - Md. Ali, Sham Firdaus (2021)
Gamma camera or also known as scintillation camera is a typical device used for image acquisition in the field of medical imaging. It is usually used as a non invasive technique to view and diagnose a patient by the reconstructed images of a human body. Current gamma camera technology typically constructed using photomultiplier tubes (PMT) is considered to be costly and space consuming. In addition to this, it also operates at a very high voltage and measurements can be affected by the existence of magnetic field. Recent research on photon detection has resulted to the introduction of silicone photomultiplier (SiPM) which operates at low voltage and insensitive to magnetic field. Generally, SiPM is a photo sensor that has great potential in replacing PMT in a gamma camera. However several elements of SiPM need to be considered. The aim of this research is to develop a gamma camera with SiPM sensor technology. Several important parameters need to be identified in modelling the gamma camera. The parameters include on configuring the optimum SiPM High Voltage Bias (Vbias) value based on the sensor’s temperature characteristic and the optimum operating distance. The research also focused in implementing the modelled gamma camera to reconstruct and evaluate the images from the experimental projection data. Several laboratory equipment and materials are used for the experiments in this research, including the Vertilon IQSP480 data acquisition reader, the Thallium doped Caesium Iodide (CsI(Tl)) crystal scintillation material, the SiPM sensor array SL4-30035 and others. The radioactive source Caesium-137 (Cs-137) is used for this research as a gamma emitting substance. Cs-137 is a common substance used for calibrating radiation equipments and radiation therapy. In addition to this, it also has a longer half life of over 30 years. Result and analysis from the experiments conducted have revealed that, the sensor bias voltage, Vbias of the SiPM needs to be set to 27.8 V at a stable operating temperature of 43 °C, in order for the sensor to only trigger in the presence of a radioactive source. Next, the radioactive source has to be placed within a 1 cm distance from the sensor to obtain the optimum measurements from the data acquisition reader. The gamma camera modelled in this research is able to capture gamma ray energy projected to the SiPM sensor by accumulating up to 120 pC of charge in duration of 10 seconds. The sensor is able produce a spatial resolution of 26% at 662 keV. It also has a detection efficiency of 14%. At a distance of 1 cm, it is able to record 1542 photon counts upon exposure to a Cs-137 point source for 60 seconds. Furthermore, evaluation of the images reconstructed from the gamma camera has also revealed that the projection data pre-processing interpolation with Gaussian method is able to produce the highest pixel luminance and contrast value. Back Projection algorithm with Ram-Lak filter is also considered to be the most suitable technique to be applied for this gamma camera in reconstructing the image of a point source gamma emitting radioactive material. In conclusion, this research has successfully developed a gamma camera using SiPM technology that can perform a 12 mm x 12 mm scanning area. It is constructed with a 4 x 4 pixel SiPM sensor and a CsI(Tl) scintillation material with a thickness of 6.35 mm. The dimension of SiPM sensor which is generally smaller in sizes in comparison with PMT is suitable in producing a mobile and portable medical imaging device in the future.